DNA Methylation and Transcriptome Profiling Reveal the Role of the Antioxidant Pathway and Lipid Metabolism in Plectropomus leopardus Skin Color Formation - Yang Liu; Linna Wang; Zhentong Li; Linlin Li; Tangtang Ding; Shuai Chen; Pengfei Duan; Xinyi Wang; Yishu Qiu; Xiaoyu Ding; Yongsheng Tian (Antioxidants)
Leopard coral grouper (Plectropomus leopardus), possessing a distinct red body color, is an important species in commercial markets; however, the high ratio of black individuals under intensive cultivation has limited the commercial value of the species. To dissect the regulatory mechanisms underlying the red skin trait in P. leopardus, gene expression and DNA methylation modifications were compared between red and black skin tissues after astaxanthin treatment. Astaxanthin effectively increased the redness value a* and body weight. Multi-omics analyses revealed the crucial roles of pathways related to antioxidants and lipid metabolism, particularly “Tyrosine metabolism”, “Melanogenesis”, “Fatty acid metabolism”, “Fatty acid elongation”, and “Biosynthesis of unsaturated acids”, in red skin coloration. A molecular network for the regulation of red skin coloration in P. leopardus was constructed, and pmel, tyr, tyrp1a, tyrp1b, dct, slc24a5, wnt1, acsl4, elovl1, elovl6l.1, elovl6l.2, and elovl7 were identified as key genes. Notably, pmel, acsl4, and elovl7 were negatively regulated by differential DNA methylation. Our results provide new insight into the molecular and epigenetic mechanisms of body color variation, representing a significant step towards breeding for the red skin trait in P. leopardus.